Access in all areas? A round-up of developments in market access and health technology assessment: part 16 - Sreeram V Ramagopalan; Annie Jullien Pannelay (Journal of Comparative Effectiveness Research, 2026)
In this update we review new evidence on the rising prevalence of prior authorization rejections, delays and denials affecting US patients seeking access to branded prescription medications. We also examine a comparative study of cost-effectiveness thresholds cited in the USA and in countries designated as comparators under the Most-Favored-Nations Executive Order.